Marketing promotion and positioning - Córdova Navarro, Clarissa Oliva (2019)
The present investigation called: PROMOTION OF THE MARKETING AND THE POSITIONING OF THE I.E. SAN JUAN MARÍA VIANNEY, CHICLAYO 2017, aims to: Evaluate the promotion of marketing and its relationship with the positioning of the Educational Institution San Juan María Vianney, Chiclayo, 2017, among the theories that underlie research we have Supported Marketing Promotion by specialists Kotler y Keller and positioning theory by the renowned Philip Kotler, the type of research was descriptive, non-experimental design, the sample was established in 103 parents, who were surveyed in a single moment to determine the perception of positioning, and the level of marketing promotion. An association was found between the marketing promotion and positioning variables of the San Juan María Viannney Educational Institution, a high and positive correlation coefficient (0.83) was observed. The association between the variables is corroborated by the significance of the hypothesis test, this is Sig. Bilateral = 0.00 <0.05.